Framework for creating an incident command center during crises. Issue 3 (October 2021) - Kaye, Alan D.; Cornett, Elyse M.; Kallurkar, Anusha; Colontonio, Matthew M.; Chandler, Debbie; Mosieri, Chizoba; Brondeel, Kimberley C.; Kikkeri, Sathyadev; Edinoff, Amber; Fitz-Gerald, Mary Jo; Ghali, G.E.; Liu, Henry; et al.
Abstract : The Hospital Incident Command System (HICS) is an incident management system specific to hospitals based on the principles of Incident Command System (ICS), and it includes prevention, protection, mitigation, response, and recovery. It plays a crucial role in effective and timely response during the periods of disasters, mass casualties, and public health emergencies. In recent times, hospitals have used a customized HICS structure to coordinate effective responses to public health problems such as the Ebola outbreak in the US and SARS epidemic in Taiwan. The current COVID-19 pandemic has placed unprecedented challenges on the healthcare system, necessitating the creation of HICS that can help in the proper allocation of resources and ineffective utilization of healthcare personnel. The key elements in managing a response to this pandemic include screening and early diagnosis, quarantining affected individuals, monitoring disease progression, delivering appropriate treatment, and ensuring an adequate supply of personal protective equipment (PPE) to healthcare staff.